Less Experienced Telestroke Consultants Are More Likely to Go On-Camera, but Less Likely to Give tPA - Adam de Havenon; Lee S. Chung; Jaleen Smith; Kirby Taylor; Jennifer J. Majersik; Nabeel Chauhan (Stroke Research and Treatment)
Background. Stroke telemedicine (telestroke) increases tPA availability and administration. However, the effective use of telestroke requires training, which is not a standard component of vascular neurology training. As a result, many providers learn telestroke skills “on the job” after finishing their training. Aims. We sought to explore if providers with more telestroke experience would be more efficient in the utilization of telemedicine, compared to providers with less experience. Methods. We prospectively collected data on telestrokes between July 2014 and July 2017 at a Comprehensive Stroke Center. Telestrokes are initiated on the telephone and typically, but not always, followed by an on-camera consult. Decision to do a phone-only versus on-camera consult is at the provider’s discretion. Results. There were 1,029 telestrokes, of which 807 were on-camera (74%). Of the 8 telestroke providers, 4 had less experience, having just finished stroke fellowship, and 4 had more experience (mean = 7.8 years of telestroke experience at the beginning of the study). Providers with less experience were more likely to go on camera than providers with more experience (79% vs. 67% of consults, p=0.021), but were less likely to give tPA when on-camera (25% vs. 33%, p=0.023). The absolute rate of tPA administration, combining phone and camera administration, or the frequency of technical difficulties were not different. Conclusions. Telestroke consultants with less experience do not triage as many cases by phone and are less likely to administer tPA on-camera, suggesting their use of telemedicine is not optimized. This supports the introduction of telestroke didactics during vascular neurology training.